Broad-spectrum and durability: understanding of quantitative disease resistance - Kou, Yanjun; Wang, Shiping (Current opinion in plant biology, 2010)
Although quantitative resistance loci provide partial and durable resistance to a range of pathogen species in different crops, the molecular mechanism of quantitative disease resistance has remained largely unknown. Recent advances in characterization of the genes contributing to quantitative disease resistance and plant–pathogen interactions at the molecular level provide clues to the molecular bases of broad-spectrum resistance and durable resistance. This emerging knowledge will help in identifying genes involved in quantitative broad-spectrum resistance and durable resistance leading to formulation of efficient ways for using these genetic resources for crop improvement. This knowledge is also turning quantitative resistance genes with minor effects into a productive resource for crop protection via biotechnological approaches.